2014
DOI: 10.1007/s00049-014-0173-2
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of the peripheral olfactory system of Western Flower Thrips, Frankliniella occidentalis towards stereoisomers of common plant volatiles

Abstract: Stereochemistry plays a significant role in structure–activity relationships of messenger chemicals. The ability to distinguish between enantiomers and geometric isomers, however, may be limited to certain stereoisomeric substances, depending on the receiver. In this study, we assessed the preference of the peripheral olfactometry system of Western Flower Thrips, F. occidentalis towards ubiquitously expressed host compounds, with a goal of establishing whether particular stereoisomers enhance host odour recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
13
0
3
Order By: Relevance
“…There is considerable evidence that chemosensation is important to host, feeding and oviposition choices made by F. occidentalis . For example, F. occidentalis detects pheromones and prefers specific plant volatiles [56, 57]. In choice tests with diverse tomato cultivars, adult female F. occidentalis preferred fully developed flowers with sepals and petals fully open to those in earlier stages of development and opening, fed preferentially on specific portions of the flower depending on tomato cultivar, and avoided specific acylsugar exudates from Type IV trichomes of tomatoes [58].…”
Section: Resultsmentioning
confidence: 99%
“…There is considerable evidence that chemosensation is important to host, feeding and oviposition choices made by F. occidentalis . For example, F. occidentalis detects pheromones and prefers specific plant volatiles [56, 57]. In choice tests with diverse tomato cultivars, adult female F. occidentalis preferred fully developed flowers with sepals and petals fully open to those in earlier stages of development and opening, fed preferentially on specific portions of the flower depending on tomato cultivar, and avoided specific acylsugar exudates from Type IV trichomes of tomatoes [58].…”
Section: Resultsmentioning
confidence: 99%
“…The responses of antennae to synthetic (-)-and (+)-enantiomers of δ-heptalactone revealed that only (-)-δ-heptalactone was EAD active while no response was registered to (+)-δ-heptalactone. Usually, receptors activated by optically active compounds show preferential of varying degrees to one of the enantiomers or respond at a similar level to both enantiomers [24][25][26][27]. Until date, no response to one enantiomer of an enantiomer pair has been reported in limited number of insect species [24,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Bir araştırmada yeşil yapraklarda bulunan uçucuların da konukçu tercihini etkilediği, cis-3-hexen-1ol, trans-3-hexen-1-ol'un (R)-limonene, (S)-limonene, (+)-terpinen-4-ol, (-)-terpinen-4-ol, (+)-borneol ve (-)borneol'e göre F. occidentalis'i daha çok cezbettiği kaydedilmiştir (Abdullah & Butt, 2015).…”
Section: Konukçu Bitki Kokularıunclassified
“…Geraniol ile kombine edilmiş mavi yapışkan tuzakların F. occidentalis bireylerini yapışkan mavi renkli tuzaklardan 1.9 kat daha fazla cezbettiği bilinmektedir (Sutliff-Shipley, 2006). Yapışkan tuzaklara kokuların ilave edilmesi F. occidentalis gibi anahtar zararlılara karşı bu tuzakların cezbediciliğini artırmakta ve kitlesel yakalama uygulamalarının daha etkili olmasını sağlamaktadır (Abdullah & Butt, 2015).…”
Section: Renk Tuzaklarının Kullanımıunclassified